First principles study of electronic, optical and transport properties of bulk and monolayer SnO. (February 2021) - Maskar, E.; Fakhim Lamrani, A.; Belaiche, M.; Es-Smairi, A.; Rai, D.P.; Fazouan, Nejma
Abstract: In this study, we used first principles calculations to investigate the influence of extracting the SnO (ML) monolayer, through electronic, optical and transport properties. Our simulation results of high optical transmission of SnO-ML comprehend the previously reported theoretical results. It shows around 96% optical transmission. These characteristics suggest that the SnO-ML is a potential material for optoelectronic and solar cell applications. In terms of thermoelectric properties, the electrical conductivity has been significantly improved at low temperature, the power factor and figure of merit are enhanced in SnO-ML. The materials' specifications considered that two-dimensional materials SnO-ML are better thermoelectric materials and may be efficient for thermoelectric energy conversion. Highlights: Applied the exact exchange-correlation potentials for treating different properties of SnO-Bulk and SnO-ML. TB-mBJ potential is better for SnO-ML.Band gap is in reasonable agreement with experimentally reported. The structural optimization and electronic properties of SnO-Bulk and SnO-ML are investigated. The optical and thermoelectric properties for SnO-ML are significantly enhanced and the transparent properties can be still maintained and attained 95%.